THE ROLE AND CHALLENGES OF ARTIFICIAL INTELLIGENCE IN INFORMATION TECHNOLOGY EDUCATION - Bai, Xuejiao (Pacific International Journal, 2024)
This paper examines the increasing role of artificial intelligence (AI) in information technology (IT) higher education and the key opportunities and challenges associated with its adoption. A review of 75-100 research studies published during 2016-2022 and industry perspectives reveals AI’s effectiveness in improving learning outcomes through personalized, adaptive systems. However, integrating AI also poses risks regarding transparency, accountability, automation, biases, accessibility, and ethical impacts. Faculty perceptions, technology readiness, curriculum reform needs, and policy implications are analyzed under a conceptual framework integrating technology adoption and AI ethics theories. Qualitative methodology entails literature analysis to highlight AI’s advantages in optimizing human teaching efforts while weighing concerns around dehumanization, data privacy, and disempowerment. Balanced policies and practices focused on developing students’ AI competencies alongside critical thinking abilities are recommended to harness AI’s potential equitably and ethically. Deliberate efforts are needed to engineer inclusion into AI systems and uphold transparency in automated decision-making. The study informs strategies for readying IT students to responsibly apply AI tools to augment human capabilities.